PARTISIPASI MASYARAKAT DALAM PENGELOLAAN SAMPAH DI DESA WISATA SERANGAN - I Made Weda Satia Negara; I Wayan Wirawan; Putu Bagus Wichitakani Wahyu C (Universitas Triatma Mulya, 2023)
Serangan tourist village as a tourism area is faced with the problem of increasing the amount of waste piles due to an increase in population and increased human activity. Waste production is increasing every day in line with the increase in population and consumption patterns. The thing that must be done to overcome the increasing volume of waste is by reducing the volume of waste at the source through empowering community participation. The problem in community participation regarding waste management is what forms of regulation are related to waste management in the Serangan Tourism Village Environment. The introduction of waste management to the community aims to introduce waste management methods in preserving and keeping the environment clean in Serangan Tourism Village. Based on the research results, one form of community participation in efforts to improve the environment is by donating labor in the form of community service and participating in waste management. Apart from that, they also held community meetings which were attended by some residents for the kelurahan level. The community carried out these activities without feeling forced at all. The level of community participation that occurred in the Serangan Village Environment according to the medium category, the community participates in waste management but the implementation is still not optimal. The important role of the community and all parties is expected for the realization of success in providing learning about community participation in waste management to maintain cleanliness in the tourist village environment.